2021
DOI: 10.1002/ange.202103657
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of First Magnesium Fluorooxoborate with Stable Fluorine Terminated Framework for Deep‐UV Nonlinear Optical Application

Abstract: The generated light can be tuned to cover almost the entire spectral range from deep‐ultraviolet to terahertz wavelengths by utilizing the nonlinear optical crystals with a simple frequency doubling process. Among them, the discovery of novel candidates for the production of deep‐ultraviolet light is by extension a great challenge toward realizing the vast potential. Actually, the availability for this process mainly depends on whether the critical performance can be well coexisted in one practical crystal. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…To date, in addition to the most commonly used NLO crystals, such as KBe 2 BO 3 F 2 15 (KBBF), etc., a series of borates containing [BOxF 4−x ] units with excellent optical properties has been reported. For example, the AB 4 O 6 F (A = NH 4 , Na, Cs) [16][17][18] and AEB 5 O 7 F 3 (AE = Mg, Ca, Sr) [19][20][21] series and BaB 4 O 6 F 2 22 all have cut-off edges below 200 nm.…”
Section: Introductionmentioning
confidence: 99%
“…To date, in addition to the most commonly used NLO crystals, such as KBe 2 BO 3 F 2 15 (KBBF), etc., a series of borates containing [BOxF 4−x ] units with excellent optical properties has been reported. For example, the AB 4 O 6 F (A = NH 4 , Na, Cs) [16][17][18] and AEB 5 O 7 F 3 (AE = Mg, Ca, Sr) [19][20][21] series and BaB 4 O 6 F 2 22 all have cut-off edges below 200 nm.…”
Section: Introductionmentioning
confidence: 99%
“…and properties (kinetic effect, linear, nonlinear optical, etc.) were well regulated. In the past few years, studies have shown that the introduction of F in borates to form fluorooxoborates can largely enrich the structural chemistry of the borate family and also accelerate the discovery of new optical materials with target properties. Structurally, the introduction of F in a regular [BO 4 ] tetrahedron to form a [BO 3 F] unit can reduce the microscopic symmetry and make the anionic framework more flexible, which might help us obtain more polymorphs with the assigned molecular formula . It should be noted that the B–O/F anionic frameworks of AB 4 O 6 F (A = NH 4 , Na, Rb, Cs) and MB 2 O 3 F 2 (M = Pb, Sn, Ba) are very flexible, and the arrangement and symmetry are heavily affected by A-and M-site cations, making them crystallize in the different noncentrosymmetric space group, indicating that fluorooxoborates might have more flexible structures when compared with pure borates without B–F bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Actuated by the rapid development of advanced technology, NLO crystals have significant applications in all-solid-lasers, laser guidance, precise micro-manufacturing, biological tissue imaging and advanced scientific instruments. [5][6][7][8][9][10][11] Over the past decades, scientists have made great efforts to explore NLO crystals and elucidate the relationship between their structures and NLO properties. Consequently, some famous NLO crystals, like β-BaB 2 O 4 (BBO), LiB 3 O 5 (LBO), KBe 2 BO 3 F 2 (KBBF), KH 2 PO 4 (KDP), KTiOPO 4 (KTP) and AgGaS 2 , have been commercialized.…”
mentioning
confidence: 99%